THE INFLUENCE OF BRAND IMAGE ON CONSUMER SATISFACTION WITH PURCHASING DECISIONS AS INTERVENING VARIABLES (Case Study on Students of STIE Bina Karya Kota Tebing Tinggi) - Benhart Nainggolan (RADJA PUBLIKA, 2023)
This study aims to determine